DEVELOPMENT OF NON-DESTRUCTIVE MONITORING SYSTEM FOR CHLORIDE PENETRATION INTO REINFORCED CONCRETE STRUCTURES - Antoni Antoni (Institute of Research and Community Outreach - Petra Christian University, 2006)
Reinforced concrete structures in marine environment are subjected to chloride penetration, which significantly degrades the structural performance due to the occurrence of corrosion in the steel reinforcement. The performance degradation of the structures would reduce the intended service life and caused higher maintenance and repair cost. Therefore, system to monitor chloride penetration into reinforced concrete before the starting corrosion of reinforcement is indispensable. An embedded probe system to detect chloride penetration into concrete was developed in Japan. This probe consists of a cementitious material body and some number of wires as sensors, which are set in the shallow ditches around the probe body. The system detect the chloride penetration by monitoring the initiation time of wire corrosion, it also has the advantages of continuous monitoring and early warning on the onset of corrosion in the reinforcement. However, the probe had not yet had high sensitivity for detecting critical chloride content in concrete. Therefore to increase its sensitivity, four types of improvements, namely partial coating of the wires, waterproofing on the probe body, filling the ditches with porous material and supplying small current on the wires were evaluated in this study. From the experimental result, it was observed that supplying small current and partial coating of the wires could improve the sensitivity of the probe significantly, while waterproofing treatment on the probe body and filling the ditches did not have significant contribution.